Stimulation of the sodium transport across the frog skin by three N-terminally extended arginine-vasopressins - Ponec, J; Bakos, P; Lichardus, B; Alexandrová, M; Lammek, B; Rekowski, P; Kupryszewski, G (General physiology and biophysics, 1990)
The standard Ussing method was used to electrophysiologically characterize the effects of three analogs of arginine-vasopressin (AVP) on the frog skin, a model Na-transporting epithelium. The analogs tested were N-terminally extended Arg8-vasopressins: Ala-AVP, Ser-Ala-AVP and Thr-Ser-Ala-AVP; synthetic Arg8-AVP was used as the reference agent. The vasopressins were applied to the basolateral side of the frog skin in concentrations ranging between 10(-8) to 10(-5) mol.l-1. All the three analogs increased both the short-circuit current (Isc) and the open-circuit transepithelial potential (Voc), and decreased the transepithelial d.c. resistance (Rt) similarly as did synthetic Arg8-AVP. The results show that N-terminal extension of the Arg8-AVP did not alter the natriferic properties of AVP.
Keywords: Sodium; techniky in vitro; epitel; fyziologie kůže; Electrophysiology; kůže; elektrofyziologie; Rana temporaria; zvířata; arginin vasopresin; Skin Physiological Phenomena; Male; Epithelium; sodík; In Vitro Techniques; Animals; Membrane Potentials; mužské pohlaví; membránové potenciály; Skin; Arginine Vasopressin